ANALYSIS OF SCOUR AROUND THE FOUNDATION PILLARS OF THE LAIS RIVER PORT, PALEMBANG CITY - Syarifudin, Achmad; Monica, Gita Farera; Rosyad, Farlin; Mulyati, Ely (Ensiklopedia of Journal, 2024)
A pillar is a substructure located in the middle of the span between two abutment which also functions to carry the loads of the superstructure  and other buildings and transmit them to the foundation and distribute them to hard subgrade. Local scouring around building occurs because the local flow pattern around river buildings is a natural process that occurs in rivers duet o the influence of river morphology or the presence of water structure that block flow, for example brodge bases, brodge pillars, abutments, river cribs, etc. The presence of these water structure cdauses changes in flow characteristics such as flow speed and turbulence, giving riset o changes in sediment transport and the occurrence of scour. Research objective: to determine the scour pattern around the foundation pillars of sungai lais harbour and effective ways to control scour. Research method: experimental by collecting primary data and secondary data. Also, research was carried out through practicums using miniature rivers.the results of research obtained the magnitude by observing the flume (channel) during the running test/ stream flow and then research was carried out on the magnitude of the channel’s base elevation before it was channeled and changes in the depth of scour after it was channeled affecting the foundation pillars above. This is influenced by the speed of the water flow, the collapse rate is also not very significant. The collapse of the outer waa occured when the flow time was 10 minutes at the end of data collection. So, the factor that influences the size of the scour around the pillar is the speed of the following flow and the material deposits carried by it.  Keywords : A Pillars, Scour, Flow Speed